Las comunidades negras en Colombia:entre la diversidad cultural,la diferencia racial y los derechos diferenciados - Bonilla, Daniel (2023)
The legal framework for Colombian people of African descent faces two conceptual problems that have important political effects in practice and that are analyzed in this article. First, these laws are questionable from the perspective of the equality principle and distributive justice. It is not clear why the only individuals and groups considered entitled to the differentiated rights granted by Law 70 and its regulatory decrees are those who live in the rural and riverside zones of the Pacific basin. Second, insofar as the legal framework for Colombians of African descent uses culture as its main pillar, two variables that are essential to unde rstanding and solving the “black issue” in Colombia have been obscured: class and race.